2017
DOI: 10.3171/2016.10.spine16197
|View full text |Cite
|
Sign up to set email alerts
|

Development of a preoperative predictive model for major complications following adult spinal deformity surgery

Abstract: OBJECTIVEThe operative management of patients with adult spinal deformity (ASD) has a high complication rate and it remains unknown whether baseline patient characteristics and surgical variables can predict early complications (intraoperative and perioperative [within 6 weeks]). The development of an accurate preoperative predictive model can aid in patient counseling, shared decision making, and improved surgical planning. The purpose of this study was to develop a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(104 citation statements)
references
References 50 publications
1
102
1
Order By: Relevance
“…Both surgeons and patients alike are interested in better tools for predicting outcomes, as it allows for more comprehensive preoperative discussions and surgical decision making. Predictive analytics has now been applied across a wide variety of topics within ASD surgery, including predicting intraoperative, 15 perioperative, 16,17 and postoperative complications and outcomes. [18][19][20][21][22][23][24][25] The majority of studies published on this topic share similar principles and methodologies in the development of their respective predictive models.…”
Section: Methodology and Statisticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both surgeons and patients alike are interested in better tools for predicting outcomes, as it allows for more comprehensive preoperative discussions and surgical decision making. Predictive analytics has now been applied across a wide variety of topics within ASD surgery, including predicting intraoperative, 15 perioperative, 16,17 and postoperative complications and outcomes. [18][19][20][21][22][23][24][25] The majority of studies published on this topic share similar principles and methodologies in the development of their respective predictive models.…”
Section: Methodology and Statisticsmentioning
confidence: 99%
“…Models have also been created to assess length of stay (LOS) 16 and major early complications. 17 In the study by Scheer et al 17 a predictive model for early complications (intraoperative and within 6 weeks postoperative) was created using 45 variables from baseline demographic, radiographic, and surgical factors for 557 ASD patients. An ensemble of decision trees was trained with 5 different bootstrapped models and internal validation was accomplished using a 70:30 data split.…”
Section: Perioperative Analytics and Outcomesmentioning
confidence: 99%
“…23 Predictive modeling is a statistical technique that represents a departure from the more traditional regression analyses; however, it affords greater flexibility by allowing patterns within the available data to create accurate, patient-specific predictions without the need to establish hypotheses or control groups a priori. 1 Through this established methodology, we have successfully developed models for accurate prediction of postoperative complications, 30 proximal junction failure and proximal junction kyphosis, 28 and length of hospital stay. 26 In the present study, the same modeling techniques were used in a large cohort of surgically treated patients with ASD to predict which patients will be likely to have better outcomes, as defined by meeting MCID thresholds for ODI and QALY improvements.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, multiple studies have demonstrated the ability to build predictive models using EMR data for major perioperative complications in spine surgery, particularly surgical site infections. [53][54][55][56][57] Other models have also been created using EMR data to predict physical disability, return to work, major complications, readmission rates, walking ability, need for inpatient rehab following spine surgery, discharge, and disposition. [58][59][60][61] More specific algorithms have been created to predict preoperative factors impacting survival, discharge, and readmission rates in patients following spine surgery for spinal metastasis.…”
Section: Clinical Prognosticationmentioning
confidence: 99%